2018
DOI: 10.32737/0005-2531-2018-4-45-47
|View full text |Cite
|
Sign up to set email alerts
|

SYNTHESIS OF 2-HYDROXYPROPYL-1,3-bis-ESTEROSULPHOIMIDES OF SACCHARIN-5- AND -6-CARBOXYLIC ACID

Abstract: The interesterification reaction of the ethyl (I) and isopropyl (II) ethers of sulphoimides of saccharin-5and -6-carboxylic acids with glycerine has been studied. The corresponding 2-hydroxypropyl-1,3-bisesterosulphoimides of saccharin-5-and-6-carboxylic acids have been synthesized. They have been characterized by elemental analysis and method of the IR spectroscopy. It has been elucidated that in use of 10% PbO catalyst per mass of glycerine a yield of purposeful product reaches its greatest value -82 and 85%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…It was found that in the IR spectra (Figure 1) of this compound there are absorption bands in the region of 1406, 1436 cm -1 bending and in the region of 2882, 2936cm -1 of the stretching vibrations of the C-H bond of the CH 2 group; stretching vibrations of the amide C=O bond in the region of 1627 cm -1 ; stretching vibrations in the region of 1283 cm -1 C-N-bond; stretching vibrations of С-О-and О-Н-bonds of alcohol in the region of 1032 cm -1 and 3289 cm -1 ; stretching vibrations of the SO 2 bond in the region of 1245 cm -1 ; stretching vibrations of the C-O bond of the ester in the region of 1107 cm -1 ; stretching vibrations of the C=O bond of the ester in the region of 1721 cm -1 ; bending vibrations of the C-H bond (751.853 cm -1 ) of the substituted benzene ring [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The synthesis of 2-hydroxypropyl-1,3-biscarboxymethylester-sulphoimide of saccharin-6-carboxylic acid was carried out according to the following scheme:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that in the IR spectra (Figure 1) of this compound there are absorption bands in the region of 1406, 1436 cm -1 bending and in the region of 2882, 2936cm -1 of the stretching vibrations of the C-H bond of the CH 2 group; stretching vibrations of the amide C=O bond in the region of 1627 cm -1 ; stretching vibrations in the region of 1283 cm -1 C-N-bond; stretching vibrations of С-О-and О-Н-bonds of alcohol in the region of 1032 cm -1 and 3289 cm -1 ; stretching vibrations of the SO 2 bond in the region of 1245 cm -1 ; stretching vibrations of the C-O bond of the ester in the region of 1107 cm -1 ; stretching vibrations of the C=O bond of the ester in the region of 1721 cm -1 ; bending vibrations of the C-H bond (751.853 cm -1 ) of the substituted benzene ring [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The synthesis of 2-hydroxypropyl-1,3-biscarboxymethylester-sulphoimide of saccharin-6-carboxylic acid was carried out according to the following scheme:…”
Section: Resultsmentioning
confidence: 99%
“…There are data in the literature that monomers with ester, acid, anhydride, amide, and hydroxyl functional groups are usually used as monomers to obtain heterocyclochain heatresistant polymers and oligomers of various structures [5][6][7][8][9][10]. Previously, we have obtained anhydride, dianhydride, and esters of sulphoimides of mono-and disaccharincarboxylic acids, which were used as monomers in the preparation of epoxyimide resins and polymeric materials [11][12][13]. There is also information on the synthesis of diester disulphoimides by transesterification of the methyl ester of saccharin-monocarboxylic acids with aliphatic and aromatic glycols [14].…”
Section: Introductionmentioning
confidence: 99%
“…35164/0554-2901-2024-02-21-23Термическую стабильность полученных соединений изучали методом дифференциально-термического анализа на дериватографе системы «Паулик-Паулик-Эрдей»[17]. Навеска образца 200 мг, чувствительность каналов: TГ -200, ДТА -250 μν, ДТГ -1 mv, скорость подъема температуры 5°С/мин в токе воздуха.Изучение физико-механических свойств производилось на разрывной машине WPM, VEB Thuringerindustriewerk, Rauenstein R-40, ТУР-2092.Результаты и их обсуждениеСинтез олиготриглицерида (ОТГ) сахарин-6-карбоновой кислоты производился путем переэтерефикации алкиловых эфиров сульфоимида сахарин-6-карбоновой кислоты с избытком 1,2,3пропантриола по следующей схеме[18]: В ИК-спектрах полученного соединения наблюдались следующие полосы поглощения: деформационные (720, 1454, 2921 см -1 ) и валентные колебания C-H-связи групп CH 2 ; валентные (1644 см -1 ) колебания C=O связи амида; валентные (1719 см -1 ) колебания C=O связи сложного эфира; валентные (1153 см -1 ) колебания С-О связи сложного эфира; валентные (1239, 1283 см -1 ) колебания SO 2 -группы; валентные (1019 см -1 ) колебания S=O связи; деформационные (1573 см -1 ) колебания N-H связи и деформационные (617, 678, 750, 859, 1607 см -1 ) колебания CH связи замещенного бензольного кольца. Широкая интенсивная полоса поглощения в интервале 3200-3550 см -1 с максимумом 3276 см -1 относится к валентным колебаниям ассоциированных гидроксильных групп.…”
unclassified